How Early-Life Gut Microbiota Alteration Sets Trajectories for Health and Inflammatory Bowel Disease? - Guo, Feilong; Cai, Demin; Li, Yanwei; Gu, Haotian; Qu, Huan; Zong, Qiufang; Bao, Wenbin; Chen, Aoxue; Liu, Hao-Yu (Frontiers in Nutrition, 2021)
Inflammatory bowel disease (IBD) is a recurrent chronic inflammatory condition of the intestine without any efficient therapeutic regimens. Gut microbiota, which plays an instrumental role in the development and maturation of the immune system, has been implicated in the pathogenesis of IBD. Emerging evidences have established that early-life events particularly maternal influences and antibiotic treatment are strongly correlated with one’s health or susceptibility to disease in later-life. Thus, it is proposed that there is a critical period of time in infancy, during which the environmental exposures bestow a long-term pathphysiological imprint. This notion sheds new lights on the development of novel approaches for the treatment, i.e., early interventions, more precisely, the prevention of many uncurable chronic inflammatory diseases, like IBD. In this review, we have integrated current evidences to describe the feasibility of the ‘able-to-be-regulated microbiota’, summarized the underlying mechanisms of the ‘microbiota-driven immune system education’, explored the optimal intervention time window, and discussed the potential of designing early-probiotic treatment as a new prevention strategy for IBD.